Oxidative ring-contraction of 3H-1-benzazepines to quinoline derivatives. Issue 49 (9th December 2015) - Karimi, Sasan; Ma, Shuai; Ramig, Keith; Greer, Edyta M.; Szalda, David J.; Subramaniam, Gopal
Graphical abstract: Abstract: When treated with SeO2, 2, 4-diphenyl-3 H -1-benzazepine (1 ) is oxidized equally at C3 and C5, giving either products of rearrangement or fragmentation; in both cases quinoline derivatives are the primary products. When C3 is oxidized, electrocyclization followed by ring-opening with phenyl migration gives the major product phenyl(3-phenylquinolin-2-yl)methanone (6 ), whereas C5 oxidation produces 2, 4-diphenylquinoline (2 ) and 1, 2-bis(2, 4-diphenylquinolin-3-yl)diselane (8 ). Oxidation of C5 in1 also results in formation of 2-(3, 5-diphenylfuran-2-yl)aniline (7 ). On the other hand, 3-methyl-2, 4-diphenyl-3 H -1-benzazepine (9 ) upon treatment with SeO2 gives primarily a product of oxidation of C3, 2, 3-diphenylquinoline (5 ). Oxidation of C5 in (9 ) is a minor pathway, and gives both 3-methyl-2, 4-diphenylquinoline (10 ) and (3-methyl-2-phenylquinolin-4-yl)(phenyl)methanone (11 ). CO was detected as a byproduct in both reactions. Although the ring-contraction reaction using SeO2 has been previously noted, no mechanistic proofs have been firmly established. In this Letter, we provide evidence for the ring-contraction of benzazepines to quinolines through a fragmentation path (loss of CO and acetic acid) or through rearrangement.